Experimental processes for optimized lighting techniques: enhancing vertical farming crop growth and yield efficiency - Linn, Riley (Kansas State University, 2024)
The demand for year-round crop production pushes farmers to find innovative solutions. Researchers are actively exploring vertical farming to determine its potential for commercial crop production. Vertical farms offer a dual advantage: they minimize the need for extensive horizontal land usage and they enable year-round crop cultivation due to their enclosed interior environments. Usually, the sun is the primary source of light for plant development, but electric lighting can accommodate further production in these applications. Recent research is developing spaces without access to sunlight, leading to electric lighting being the only source of light exposure for plant growth. This report investigates the relationship between lighting and plant growth, seeking the optimal lighting conditions for controlled vertical farming environments. Experimental recommendations for optimal lighting conditions for various crops, including strawberries, lettuce, peppers, and tomatoes, are provided. Using Light Emitting Diode (LED) technology, recommendations for specific wavelengths, intensity, and duration are assessed. The ability to change the conditions will impact plant development and provide the ideal conditions for each crop. The various combinations are determined to find the most significant production yield, whether growth or fruit production. This report will consider the effects of photosynthetic photon flux density (PPFD), crop photoperiods, color of light exposure, and plant production. These will be the primary determinations for growth for this experiment. The report begins with an overview of the connection between lighting design and horticulture over the years. This historical perspective helps to contextualize the significance of lighting in plant growth and development, highlighting the evolution of lighting technologies and their applications in agriculture. It also explores the pivotal role of light intensity, duration, and quality in influencing photosynthesis, flowering, and overall crop yield. This section sets the stage for a comprehensive examination of the impacts of lighting on various aspects of plant biology. Delving into the experimental framework involves assessing the effects of different light spectra on the growth patterns of diverse plant species as our specific objectives. The measurement methodologies above will allow us to closely monitor and quantify the responses of each plant species to distinct lighting treatments, thereby facilitating a thorough analysis of the relationships between light and growth. The lighting in the controlled environment is specified, including fixture descriptions, output values for intensity, source color, and the control system used in the experiment. Each source will emit light of varying spectra and intensity, allowing us to investigate the unique effects of different wavelengths on plant physiology. Detailed information about these light sources' spectral characteristics, including peak wavelengths and spectral distribution, is provided. Once the experimental setup is defined, hypotheses for each crop are formulated, specifying their assumed reactions. These hypotheses guide the analysis of the anticipated responses from each plant species under the specified lighting conditions. By systematically assessing how plants respond to various wavelengths and durations of light exposure, the aim is to provide valuable insights that can inform optimized lighting strategies for horticultural practices. Furthermore, the report discusses the potential practical applications of the findings, which could contribute to more efficient and sustainable crop production methods.
Keywords: Lighting; Horticulture; Vertical farm; PPFD; Photoperiod; PAR